System requirements analysis - Grady, Jeffrey O. (Elsevier insights, 2014)
This book gives professional systems engineers the tools to set up proper and effective analyses of the resources, schedules and parts needed to successfully undertake and complete large, complex projects. This fully revised text offers readers the methods for rationally breaking down a large project into a series of stepwise questions, enabling them to determine a schedule, establish what needs to be procured, how it should be obtained, and what the likely costs in dollars, manpower, and equipment will be to complete the project at hand. It covers various analytical approaches to system requirements, including structural and functional analysis, budget calculations, and risk analysis. This resource is compatible with the full range of popular engineering management tools, from project management to competitive engineering to Six Sigma, and will ensure that a project gets off to a good start before it's too late to make critical planning changes. The book can be used for either self-instruction or in the classroom, offering a wealth of detail about the advantages of requirements analysis to the individual reader or the student group.--Edited summary from book.